Cervical Cancer Risk Factors Association in Patients at the Gynecologic-Oncology Clinic of Dr. Soetomo Hospital Surabaya - Aisyiah Rahmi Putri; Siti Khaerunnisa; Indra Yuliati (National Cancer Center - Dharmais Cancer Hospital, 2019)
Background: Cervical cancer ranks fourth of all cancers in women worldwide and linked to human papillomavirus (HPV) infection. Despite the evidence of methods for cervical cancer prevention, such as pap smear test and HPV vaccination, most of the women remain unscreened and never get HPV vaccination. Most cervical cancer cases are not diagnosed early enough, leading to poor outcomes. This study aims to examine the association of risk factors with cervical cancer incidence in Dr. Soetomo Hospital Surabaya and also records the patients’ knowledge of cervical cancer preventions, history of HPV vaccination, and pap smear screening test.Methods: This is a case-control study. Questionnaires were given to 60 newly diagnosed cervical cancer patients and 60 non-cervical cancer patients at The Gynecologic-Oncology Clinic of Dr. Soetomo Hospital Surabaya in the period of March 2016 until August 2016. The analysis was made using bivariate and multivariate logistic regression analysis.Results: The bivariate logistic regression analysis confirmed that parity more than two times (p=0.001), history of birth control pills consumption more than 10 years (p=0.04), passive smoking (p=0.001) and not knowing that cervical cancer can be prevented (p=0.001) were significantly associated to the incidence of cervical cancer. The multivariate logistic regression analysis confirmed that not knowing that cervical cancer can be prevented (OR=6.85), the history of passive smoking (OR=4.04), parity more than two times (OR=2.89) and history of birth control pills consumption more than 10 years (OR=6.52) were the independent factors that were associated with the cervical cancer incidence.Conclusions: Parity more than two times, history of birth control pills consumption more than 10 years, history of passive smoking, not knowing that cervical cancer can be prevented and never having a pap smear test were the factors associated with cervical cancer incidence.